One-Dimensional Magnetic FeCoNi Alloy Toward Low-Frequency Electromagnetic Wave Absorption - Yang, Bintong; Fang, Jiefeng; Xu, Chunyang; Cao, Hui; Zhang, Ruixuan; Zhao, Biao; Huang, Mengqiu; Wang, Xiangyu; Lv, Hualiang; Che, Renchao (Nano-micro letters, 2022)
Highlights A novel FeCoNi carbon fiber (FeCoNi/CF) is obtained through an improved electrospinning technology, which greatly endows the fiber with strong magnetic property. The FeCoNi/CF exhibits an enhanced electromagnetic loss capability due to the construction of one-dimensional magnetic FeCoNi alloy. The designed one-dimensional FeCoNi/CF exhibits excellent performance, with a broad effective absorption band of 1.3 GHz in the low-frequency electromagnetic field at an ultrathin thickness of 2 mm, which provides a great potential for practical application in the future. Rational designing of one-dimensional (1D) magnetic alloy to facilitate electromagnetic (EM) wave attenuation capability in low-frequency (2–6 GHz) microwave absorption field is highly desired but remains a significant challenge. In this study, a composite EM wave absorber made of a FeCoNi medium-entropy alloy embedded in a 1D carbon matrix framework is rationally designed through an improved electrospinning method. The 1D-shaped FeCoNi alloy embedded composite demonstrates the high-density and continuous magnetic network using off-axis electronic holography technique, indicating the excellent magnetic loss ability under an external EM field. Then, the in-depth analysis shows that many factors, including 1D anisotropy and intrinsic physical features of the magnetic medium-entropy alloy, primarily contribute to the enhanced EM wave absorption performance. Therefore, the fabricated EM wave absorber shows an increasing effective absorption band of 1.3 GHz in the low-frequency electromagnetic field at an ultrathin thickness of 2 mm. Thus, this study opens up a new method for the design and preparation of high-performance 1D magnetic EM absorbers.